PENGARUH KECERDASAN INTELEKTUAL ( IQ ) DAN KECERDASAN EMOSIONAL (EQ) TERHADAP PRESTASI KERJA KARYAWAN UNIVERSITAS KANJURUHAN MALANG - Arien Anjar Puspitosari Suharso (Kompetensi (Competence : Journal of Management Studies), 2015)
The purpose of this study was to describe the intellectual, emotional intelligence and employee performance Kanjuruhan University of Malang, analyzing the effect of variable intellectual intelligence and emotional intelligence on employee performance Kanjuruhan Malang University administration, and analyze the dominant variable on employee performance administration Kanjuruhan University of Malang . The hypothesis of the study is 1) alleged no significant effect among variables of intellectual intelligence (IQ) and emotional intelligence (EQ) on employee performance, 2) variable alleged intellectual intelligence (IQ) has dominant influence on employee performance. Type of research is explanatory research that explains the causal relationships between variables through hypothesis testing. The location of this research at the University of Malang Kanjuruhan census method and the number of respondents 50 employees are educated scholar. The technique of collecting data using questionnaires. The analysis model used is multiple linear regression that aimed to determine the correlation between intellectual intelligence and emotional intelligence on employee performance administration Kanjuruhan University of Malang. Based on F test can be seen that the intelligence and emotional intelligence simultaneous influence on employee performance. Based on the t test can be seen that the partial intelligence and emotional intelligence impact on employee performance so that the first hypothesis is accepted. Furthermore, of the standardized beta values, intellectual variables is greater than the emotional intelligence can thus be said that the intelligence variables have a dominant influence on the administration of employee performance so that the second hypothesis is accepted.